Chapter 9 The interplay between policy and funding - Coriat, Anne-Marie (Taylor & Francis, 2021)
Whilst there are many common features in doctoral training across the world, there is considerable variation in how training is delivered, funded and supported. Approaches vary depending on the nature of the degree, on policies set at the national, institution and funder level and according to the nature of the financial support available. How then can we look at the interplay between funding and policy? This chapter sets out some of the issues affecting the current research system. Using the case study of Wellcome's 2017 review of doctoral training, I explain how taking a systemic view can provide insight into the culture of the research system overall. I explain how the review enabled Wellcome to deliberatively design policy and practice with an explicit intent to support a more positive culture for PhD training. I reflect on how, using a social sciences approach, this experimental approach will help evolve our understanding of how such changes in policy and practice are experienced.